2016
DOI: 10.1590/1413-70542016403033315
|View full text |Cite
|
Sign up to set email alerts
|

Phenology, yield and fruit quality of 'Paluma' guava tree at different pruning times

Abstract: Pruning guava trees at different times is an important management tool that allows year-long staggering of fruit production. In this context, this study aimed to evaluate the phenological characteristics, yield and fruit quality of the 'Paluma' guava tree at different pruning times in Botucatu, SP. The study used a completely randomized design with four treatments, four replicates and a useful experimental plot plant. The treatments consisted of four different pruning times, August 27, September 11, September … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…In the present study, organic acids including cis -aconitic acid, glutaric acid, argininosuccinate, succinyladenosine, fumaric acid, and malate increased significantly by 2.42-, 3.13-, 3.65-, 2.41-, 2.37-, and 2.58-fold, respectively, in lateral roots of pruned plants. This is consistent with an earlier report that pruning significantly increases the concentration of organic acids in guava plant . Organic compounds serve as chelating ligands, which form complexes with minerals, thereby influencing nutrient absorption .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, organic acids including cis -aconitic acid, glutaric acid, argininosuccinate, succinyladenosine, fumaric acid, and malate increased significantly by 2.42-, 3.13-, 3.65-, 2.41-, 2.37-, and 2.58-fold, respectively, in lateral roots of pruned plants. This is consistent with an earlier report that pruning significantly increases the concentration of organic acids in guava plant . Organic compounds serve as chelating ligands, which form complexes with minerals, thereby influencing nutrient absorption .…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with an earlier report that pruning significantly increases the concentration of organic acids in guava plant. 27 Organic compounds serve as chelating ligands, which form complexes with minerals, thereby influencing nutrient absorption. 28 It is reported that increased organic acids in roots enhance the uptake of phosphate from the soil.…”
Section: ■ Discussionmentioning
confidence: 99%
“…According to Pereira [51] and Silva et al [52], for exclusively economic reasons, the months from October to February are recommended in Brazil as the best season for pruning aimed at fruit production, thus making better use of the periods with higher fruit demand. Guava plants can show budding problems or flaws in months with milder temperatures, normally from May to July [49,53].…”
Section: Discussion Fruit Pruning and Thinning Improves Gas Exchange ...mentioning
confidence: 99%
“…It is also observed that pruning during the vegetative phase (September to November) implies leaf elimination, which are organs that synthesize organic substances, determining the productivity of the crop. Although the remaining leaves increase their photosynthetic efficiency as part of the plant's effort to balance photosynthetic demand, this is insufficient to compensate for the production of photosynthesis at the previous levels, thus resulting in a weakening effect of pruning [50,52].…”
Section: Discussion Fruit Pruning and Thinning Improves Gas Exchange ...mentioning
confidence: 99%
“…It is a popular fruit tree of tropical and subtropical climate and is native to Tropical America stretching from Mexico to Peru. It belongs to family Myrtaceae [1][2][3]. The guava is classified under genus Psidium that contains 150 species but only Psidium guajava is exploited commercially.…”
Section: Introductionmentioning
confidence: 99%